Simultaneous microarray measurement of nuclear and whole cell changes in gene expression reveals overlapping but distinct patterns of transcriptional regulation - Cheadle, Chris (Henry Stewart Talks, 2009)
Conceptual frameworks for the interpretation of gene expression data, Microarray data analysis, The potential transcriptome space is n-dimensional, Co-ordinate gene expression, Evolution of current microarray technology, Northern blots, Radioactivity on nylon, Combined analysis of conventional microarray with NRO array, Jurkat T cell activation, Global comparison of whole cell mRNA vs. nascent gene transcription
Archived at 2021/02/25